Pendidikan Inter-Religius Perspektif Al-Qur’an - Imronudin Imronudin (Alim | Journal of Islamic Education, 2021)
The conclusion of this research is that inter-religious education is education that encourages all students to have an intellectual, moral, achievement and noble personality with humanity and togetherness oriented to develop the principles of democracy, equality and justice in social life. Students are required to know the background of each religion and not see it from just one perspective, but also through the perspectives of others to avoid excessive fanaticism in religion that can be a trigger for conflict so far. The above definition is based on Inter-Religious values ​​in the Qur'an, namely: musyawarah (Surah Ali Imron/3: 159), al-musawah (Surah An-Nisa/4: 58), al-‘adl (Surah al-Maidah/5: 8, Surah al-Nahl/16: 90), al-ta’aruf (Surah al-Hujarat / 49: 13), al-ta’awun (Surah al-Maidah/5: 2 ), hablum min an-nas (QS. an-Nisa/4: 36), tasamuh (Surah al-Baqoroh/2: 256, Surah Yunus/10: 99, Surah Al-Maidah/5: 48) and rahmatan lil ‘alamin (QS Al-Anbiya / 21: 107). There are at least two things that are needed in the construction of Inter-Religious Education in schools, namely; dialogue by placing each of the religions that are in an equal position. And next is to develop an attitude of tolerance to provide opportunities for each religion to understand each other